2007
DOI: 10.3171/jns.2007.106.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Selective subtemporal amygdalohippocampectomy for refractory temporal lobe epilepsy: operative and neuropsychological outcomes

Abstract: Subtemporal selective amygdalohippocampectomy provides favorable surgical and neuropsychological outcomes and does not cause significant postoperative decline of verbal memory if performed on the language-dominant side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 30 publications
1
46
1
1
Order By: Relevance
“…In contrast, Hori et al 7 reported no loss of verbal memory in their patients; there were no significant differences in verbal memory between patients who underwent surgery on the dominant hemisphere and those who underwent surgery on the nondominant hemisphere, and there was no significant loss of memory postoperatively compared with preoperatively. In addition, some other studies in which subtemporal SAH was performed also reported no loss of verbal memory.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In contrast, Hori et al 7 reported no loss of verbal memory in their patients; there were no significant differences in verbal memory between patients who underwent surgery on the dominant hemisphere and those who underwent surgery on the nondominant hemisphere, and there was no significant loss of memory postoperatively compared with preoperatively. In addition, some other studies in which subtemporal SAH was performed also reported no loss of verbal memory.…”
Section: Discussionmentioning
confidence: 74%
“…4 By drilling away the retrolabyrinthine presigmoid petrosal bone, at least 1 cm more space below and 1 cm more space medially was obtained than in the conventional subtemporal approach, and temporal retraction pressure was diminished. In a subsequent report of 26 cases, 7 there were encouraging neuropsychological and seizure outcomes. There were no injuries to any bridging veins, including the vein of Labbé.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach, directed through the occipitotemporal gyrus or the collateral sulcus on the inferior surface of the temporal lobe, has been used to access the posterior part of the hippocampus and the inferior part of the atrium for amygdalohippocampectomy without any visual or memory deficits. 39,48,84 Based on our dissections, the Li-Am fasciculus may be damaged in this approach ( Fig. 16; Table 3).…”
Section: 573112mentioning
confidence: 99%